Adição de coenzima Q10 e melatonina em diluente para congelação de sêmen ovino - Tironi, Stella Maris Teobaldo [UNESP] (2021)
Oxidative stress can affect sperm quality during freezing. The aim of this experiment was to observe the effect of Coenzyme Q10 (CoQ10) and Melatonin addition in seminal extender on the sperm quality and pregnancy rate in sheep. Experiment 1: Ejaculates of 2 crossbred rams were used in 5 repetitions, forming 7 treatments: Control (pure seminal extender), C1 (0,175mM of CoQ10), C3 (0,35mM of CoQ10), C7 (0,7mM of CoQ10), M0,5 (0,5mM of melatonin), M1 (1mM of melatonin), M2 (2mM of melatonin). Semen was evaluated by computerassisted sperm analysis (CASA) at 0, 1, 2 and 3h, considering total motility (TM), progressive motility (PM) and percentage of rapid spermatozoa (PRS). Experiment 2: Ejaculates of 8 Dorper rams were used in triplicate, testing 4 treatments: Control (pure seminal extender), C1 (0,175mM of CoQ10), C3 (0,35mM of CoQ10) and C7 (0,7mM of CoQ10). Complete sperm analysis was performed after thawing by CASA and analysis of integrity and stability of plasma and acrosomal membranes, lipid peroxidation, mitochondrial potential and super oxide anions production by flow cytometry at 0 and 2h. Altogether, 198 ewes were inseminated by laparoscopy, divided into two treatments: control (n=98) e C7 (n=100), with subsequent pregnancy diagnosis. In experiment 1, all treatments were statistically inferior to control for TM parameter. Group C1 was statistically equal to control and other treatments were statistically inferior when compared to control for parameters PM and PRS. All treatments with melatonin were significantly lower, for all parameters evaluated at all moments. Regarding the moments, a difference was observed between all the evaluation moments for all parameters with a linear fall between the moments. It is concluded that CoQ10 were slightly superior to those of melatonin. In experiment 2 the parameters of TM, VAP and PRS of control group showed a statistical difference (p<0,05) between moments 0 and 2h. C3 group was statistically superior for the VAP parameter, analyzed by CASA. Animals 4, 7 and 8 were superior for the parameters TM, PM and PRS, being selected for artificial insemination stage. At moment 0h in flow cytometry, C7 group showed a higher percentage of cells with high mitochondrial potential (p<0,05). At 2h, C1 and C7 groups were statistically higher and C3 lower compared to the control. A higher pregnancy rate was observed for C7 (52%) when compared to the control (38%). It is concluded that CoQ10 is able to protect sperm cell and increase the pregnancy rate in sheep consequently